Estimation of the Compression Strength and Surface Roughness of the As-Built SLS Components Using Weibull Distribution - Khan, Hamaid Mahmood; Tarakçı, Gürkan; Bulduk, Mustafa Enes; Koç, Ebubekir (Yıldız Teknik Üniversitesi, 2021)
Selective laser sintering (SLS) is a process of fabrication of three-dimensional structures by fusing powder particles using a guided laser source. The uncertainty in the mechanical properties of the SLS parts fabricated at the same time and with the same process parameters can affect the repeatability of the SLS process. A vast difference in the mechanical properties of the concurrently processed parts can lower the production quality of the batch. Therefore, the parameters are required to be design based on the most probable outcome of the desired properties. Weibull distribution is one such statistical-based probability distribution method to measure the likelihood of the occurrence of a value of any random variable falling within a particular range of values. Here, the Weibull distribution was used to measure the relative likelihood (90% probability) of the surface roughness and the compressive strength values of the SLS-built polyamide PA2200 components in the given sample space that was obtained from 20 random samples. The results show that the variance in the surface roughness (scan and built plane) and the compressive strength values were in the range of 6–7 µm and around 10 MPa, respectively. Moreover, the surface roughness of the two orthogonal planes with 90% reliability was measured at 14.81 µm (scan plane) and 12.15 µm (built plane). Similarly, the yield strength and the compressive strength with 90% reliability were found 25.87 MPa and 62.64 MPa, respectively.
Keywords: Compression Testing; PA2200; Selective Laser Sintering; Surface Roughness; Weibull Distribution